The Longitudinal Associations Among Temperament, Parenting, and Turkish Children's Prosocial Behaviors. Issue 4 (19th June 2017) - Laible, Deborah J.; Kumru, Asiye; Carlo, Gustavo; Streit, Cara; Selcuk, Bilge; Sayil, Melike
Abstract : In Turkey, responsive behaviors toward kin are expected from children. Despite this, we know little about the factors that influence young Turkish children's prosocial behaviors. The goal was to explore how temperament and parenting are related to children's prosocial development in Turkey. A total of 293 Turkish children ( M age  = 49 months; 48.12% females) were followed up for 3 years. Mothers completed measures of their child's prosocial behaviors, as well as measures of their warmth, inductive reasoning, and the child's approach and reactivity. Maternal warmth predicted children's reactivity, and maternal induction predicted children's sociability. Children's reactivity was inversely related to children's helping behavior and sociability was related to more prosocial behavior. Maternal warmth had indirect links with helping through lessening children's reactivity. Abstract : The title for this Special Section isPositive Youth Development in Diverse and Global Contexts, edited by Emilie Phillips Smith, Anne C. Petersen, and Patrick Leman